En español! - Gahala, Estella; McDougal, Littell (Evanston, Ill. McDougal Littell, 2000)
"En español is a multi-level Spanish program for middle school and high school that provides a balanced approach to proficiency and grammar along with interdisciplinary features and projects to build confident communicators."
Includes indexes.
Levels 1-3.
Grades 9-12.
Keywords: Spanish language -- Study and teaching (Secondary); Spanish language -- Textbooks for foreign speakers -- English; Spanish language -- Grammar